Computation of flow and heat transfer through a severely stenosed carotid artery : part-1 - Yip, Yun Feng (2019)
Carotid Stenosis has been a major issue as it is one of the major causes of stroke. Thus, early detection of this disease can save lives. The study attempts to investigate the relationship between the blood pulse and temperature variation on the skin surface due to the obstruction of blood flow. Using the commercial software ANSYS Fluent, simulations were done on an idealised carotid artery geometry that has blockage of 0% and 75% in the Internal Carotid Artery. The simulations, with appropriate grid density, explore the difference that cooling, followed up by rewarming, has on the skin tissue. Results, which observed the temperature contour on the top skin, shows the developing of large cold spots on the top skin of 75% Block as compared to the 0% Block.